Fuzzy Generalized Conformable Fractional Derivative - Atimad Harir; Said Melliani; Lalla Saadia Chadli (Advances in Fuzzy Systems)
We give a new definition of fuzzy fractional derivative called fuzzy conformable fractional derivative. Using this definition, we prove some results and we introduce new definition of generalized fuzzy conformable fractional derivative.